Description of the larva of Micrathyria paulsoni González-Soriano, 2020 (Odonata: Libellulidae) - Novelo-Gutiérrez, Rodolfo; Arce-Pérez, Roberto (Zootaxa, 2021)
The last instar larva of Micrathyria paulsoni González-Soriano, 2020 is described and illustrated in detail based on specimens collected in Veracruz State, Mexico. It is compared with the larvae of M. didyma (Selys in Sagra, 1857) and M. hypodidyma Calvert, 1906, all of them belonging into the “Micrathyria didyma” group. The main structural features of M. paulsoni larva are 9–10 long premental setae plus 4–5 small setae, palpal setae 10, legs banded, a large, submedian, dark spot on each side of a pale middorsal line on S6–9, S8–9 with a posterolateral spine, larger in S9.